Blood pressure normalization via pharmacotherapy improves cutaneous microvascular function through NO‐dependent and NO‐independent mechanisms. (7th October 2017) - Craighead, Daniel H.; Smith, Caroline J.; Alexander, Lacy M.
Abstract: Hypertension is associated with endothelial dysfunction and vascular remodeling. Objective: To assess effects of antihypertensive pharmacotherapy on eNOS‐ and iNOS‐dependent mechanisms and maximal vasodilator capacity in the cutaneous microvasculature. Methods: Intradermal microdialysis fibers were placed in 15 normotensive (SBP 111±2 mm Hg), 12 unmedicated hypertensive (SBP 142±2 mm Hg), and 12 medicated hypertensive (SBP 120±2 mm Hg) subjects. Treatments were control, iNOS‐inhibited (1400w), and NOS‐inhibited (l ‐NAME). Red cell flux, measured during local heating (42°C) and ACh dose‐response protocols, was normalized to CVC (flux MAP −1 ) and a percentage of maximal vasodilation (%CVCmax ). Results: Compared to normotensives, ACh‐mediated vasodilation was attenuated in the hypertensive ( P <.001), but not in medicated subjects ( P =.83). NOS inhibition attenuated ACh‐mediated vasodilation in normotensives compared to hypertensive ( P <.001) and medicated ( P <.001) subjects. With iNOS inhibition, there was no difference in ACh‐mediated vasodilation between groups. Compared to the normotensives, local heat‐induced vasodilation was attenuated in the hypertensives ( P <.001), but iNOS inhibition augmented vasodilation in the hypertensives so this attenuation was abolished ( P =.31). Compared to normotensives, maximal vasodilator capacity was reduced in the hypertensive ( P =.014) and medicated subjects ( P =.004). Conclusions: In the cutaneous microvasculature, antihypertensive pharmacotherapy improved endothelial function through NO‐dependent and NO‐independent mechanisms, but did not improve maximal vasodilator capacity.